1998
DOI: 10.4039/ent130235-2
|View full text |Cite
|
Sign up to set email alerts
|

RESISTANCE TO THE FLEA BEETLE PHYLLOTRETA CRUCIFERAE (COLEOPTERA: CHRYSOMELIDAE) IN FALSE FLAX, CAMELINA SATIVA (BRASSICACEAE)

Abstract: The Canadian Entomologist 130: 215 -229 (1998) We carried out a 2-year study to elucidate the biology of the gregarious, idiobiont ectoparasitoid Elachertus cacoeciae (Howard) by placing (implanting) laboratoryreared spruce budworm larvae [Choristoneura fumferana (Clemens)] on curreatyear balsam fir (Abies balsamea L.) shoots in the field, simulating low (endemic) densities of the budworm. Spring female E. cacoeciae attacked fourth-, fifth-, and sixth-instar budworm larvae, beginning near the predicted peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
(41 reference statements)
4
12
0
Order By: Relevance
“…In contrast, no feeding damage was noted in the C. sativa plots even though flea beetles were observed on the plants. High resistance to flea beetle feeding has been reported for C. sativa (Pachagounder et al 1998;Soroka et al 2003), although the resistance may have resulted from the absence of cues that initiate feeding rather than a feeding deterrent (Pachagounder et al 1998). Blackleg disease [Leptosphaeria maculans (Desmaz.)…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no feeding damage was noted in the C. sativa plots even though flea beetles were observed on the plants. High resistance to flea beetle feeding has been reported for C. sativa (Pachagounder et al 1998;Soroka et al 2003), although the resistance may have resulted from the absence of cues that initiate feeding rather than a feeding deterrent (Pachagounder et al 1998). Blackleg disease [Leptosphaeria maculans (Desmaz.)…”
Section: Discussionmentioning
confidence: 99%
“…Camelina is tolerant to many insect pests such as the crucifer flea beetle (Phyllotreta cruciferae Goeze (Coleoptera: Chrysomelidae)) (Pachagounder et al, 1998;Henderson et al, 2004) and the cabbage root fly (Delia brassicae Wiedemann (Diptera: Anthomyiidae)) (Finch, 1978). Camelina is also resistant to blackleg (Leptosphaeria maculans (Desmaz.)…”
Section: Pests and Diseasesmentioning
confidence: 99%
“…Interestingly, camelina was "rediscovered" in the last decade and has gained considerable research attention, as demonstrated by the high number of recently published scientific papers (reviewed in Berti et al, 2016) and the considerable number of large EU-funded projects (i.e., ICON; ITAKA, CORE, COSMOS), funded either within the FP7 (Framework Program 7) or Horizon 2020. In North America, camelina has been identified as a promising oilseed crop in view of relatively low agricultural input requirements (Ehrensing and Guy, 2008;Obour et al, 2015;Robinson, 1987), resistance to common Brassica pests (Carcamo et al, 2007;Deng et al, 2004;Pachagounder et al, 1998;Singh and Sachan, 1997), and diseases (reviewed in: Séguin-Swartz et al, 2009;Vollmann and Eynck, 2015), as well as tolerance to drought (Hunsaker et al, 2011(Hunsaker et al, , 2013 and low temperature (Putnam et al, 1993).…”
Section: Introductionmentioning
confidence: 99%